2008
DOI: 10.1007/s12020-008-9108-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related differences in the clinical presentation of malignant and benign pheochromocytoma

Abstract: Signs and symptoms associated with pheochromocytomas are predominantly caused by catecholamine excess, but tend to be highly variable and non-specific. In this study, we evaluated 23 male and 35 female pheochromocytoma patients for symptoms and signs of pheochromocytoma with special regard to gender-related differences in presentation. Total symptom score comparison between genders showed significant differences (12.0 vs. 7.8, P-value 0.0001). Female patients reported significantly more headache (80% vs. 52%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…In keeping with this concept, patients with epinephrine-producing adrenergic tumors were characterized by an overall higher symptom score and in particular more tremor, pallor and panic/anxiety than patients with PPGLs that did not produce epinephrine. Other findings consistent with those of previous reports include the higher ages of disease presentation for patients with adrenergic than other PPGLs (33), higher reported prevalence of signs and symptoms in females than males (34), and the expectedly higher prevalences of hypertension and biochemical indices of catecholamine excess in patients with PPGLs suspected due to signs and symptoms compared to other indications (11,23). .…”
Section: Discussionsupporting
confidence: 90%
“…In keeping with this concept, patients with epinephrine-producing adrenergic tumors were characterized by an overall higher symptom score and in particular more tremor, pallor and panic/anxiety than patients with PPGLs that did not produce epinephrine. Other findings consistent with those of previous reports include the higher ages of disease presentation for patients with adrenergic than other PPGLs (33), higher reported prevalence of signs and symptoms in females than males (34), and the expectedly higher prevalences of hypertension and biochemical indices of catecholamine excess in patients with PPGLs suspected due to signs and symptoms compared to other indications (11,23). .…”
Section: Discussionsupporting
confidence: 90%
“…Based on our definition for hypertension, 4 articles were excluded because they were done before 1993, and the definition of hypertension was not specified, and there was no answer to our email for definition. All-but one-of the studies were based on medical records of the patients; the study of W. Lai et al [ 19 ] was based on questionnaire from the patients after diagnosis of pheochromocytoma, which could make recall bias; so, this study was excluded from data analysis. Finally, 37 articles were analyzed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some have indicated that patient sex may influence the chance of malignancy but this seems unlikely [16,24,25]. By contrast, persistent hypertension post-operatively increases the risk of malignancy (HR 5.3; P B 0.01) as it may represent occult metastases [11,23].…”
Section: Patient and Tumor Characteristicsmentioning
confidence: 99%